The effect of molecular weight on the biodistribution of hyaluronic acid radiolabeled with 111In after intravenous administration to rats - Svanovský, Evžen; Velebný, Vladimír; Lázníčková, Alice; Lázníček, Milan (European journal of drug metabolism and pharmacokinetics, 2008)
Hyaluronic acid (HA), is a high molecular weight (HMW) glucosaminoglycan with significant acitivity, and which influences a number of physiological and pathological processes such as tumorogenesis, arthritis, etc. The aim of this study was to determine the difference in the biodistributional pathways of 111In-labeled diethylenetriaminepentaacetic acid-hyaluronic acid (111In-DTPA-HA) molecule of three different MWs (10, 100 and 450 kDA) in a rat model, and to determine possible relationships between the biodistribution and the MW of the investigated agent for future medical applications. 111In-DTPA-HA was prepared by mixing activated DTPA and activated HA, then adding 111InCl3 to the previously prepared mixture at pH 5,5 in an acetic buffer. Biodistributional studies were performed using 36 male Wistar rats aged 2 months and weighing 280 - 350 g. The radioactivity in the samples was measured via a radiometer and the radioactivity in the different organs, blood, plasma and urine was determined. It was found that 50-54% for 10 and 100 kDa and 80% for 450 kDa of the administered dose of radiolabel was present in the liver after 5 min. Other organs show no significant increase during the experimental period. The elimination of the radiolabel was mostly renal and in low molecular weight (LMW) form. Radioactivity remained in liver throughout the 72h experimental period. A difference in the biodistribution of 450 kDa and LMW radiolabeled molecules was found. Higher amounts of radiolabel were taken up by the liver when the 450 kDa molecule was used. LMW fractions were found in the urine, and could have been a product of non-enzymatic cleavage. The extended retention of radiolabel in the liver could be related to changes in the polarity of DTPA-HA molecules.
Keywords: Chromatography, High Pressure Liquid; Metabolic Clearance Rate; Drug Stability; molekulová hmotnost; injekce intravenózní; biologická dostupnost; tkáňová distribuce; metabolická clearance; financování organizované; krysa rodu Rattus; Indium Radioisotopes; Financing, Organized; zvířata; potkani Wistar; Biological Availability; Rats, Wistar; Male; kyselina pentetová; radioizotopy india; kyselina hyaluronová; Drug Compounding; příprava léků; Rats; stabilita léku; Animals; Injections, Intravenous; mužské pohlaví; Hyaluronic Acid; Pentetic Acid; vysokoúčinná kapalinová chromatografie; Tissue Distribution; Molecular Weight